2016
DOI: 10.1002/eji.201545861
|View full text |Cite
|
Sign up to set email alerts
|

Leptin directly promotes T‐cell glycolytic metabolism to drive effector T‐cell differentiation in a mouse model of autoimmunity

Abstract: Upon activation, T cells require energy for growth, proliferation and function. Effector T cells (Teff), such as Th1 and Th17, utilize high levels of glucose uptake and glycolysis to fuel proliferation and function. In contrast, Treg instead require oxidative metabolism to fuel suppressive function. It remains unknown how Teff/Treg metabolism is altered in settings of malnutrition, when nutrients are limited and circulating leptin levels are low. We therefore examined the role of malnutrition and associated hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(121 citation statements)
references
References 49 publications
3
116
0
1
Order By: Relevance
“…Leptin supresses regulatory T cell differentiation and is a key regulator of T effector cells differentiation, such as Th17. Leptin is necessary for HIF‐1α expression, which is important for the up‐regulation of glycolytic metabolism in effector T cells …”
Section: Adipose Tissue Resident Mϕs In Obesitymentioning
confidence: 99%
“…Leptin supresses regulatory T cell differentiation and is a key regulator of T effector cells differentiation, such as Th17. Leptin is necessary for HIF‐1α expression, which is important for the up‐regulation of glycolytic metabolism in effector T cells …”
Section: Adipose Tissue Resident Mϕs In Obesitymentioning
confidence: 99%
“…Aerobic glycolysis and the induction of one or more PDKs has also emerged as potential therapeutic targets for DCA in chronic inflammatory states associated with autoimmune disease (Gerriets, et al, 2016; Gerriets, et al, 2015), obstructive pulmonary disease (Calvert, et al, 2008; Mercken, et al, 2009; Ostroukhova, et al, 2012), coronary artery restenosis (Deuse, et al, 2014) and amyotrophic lateral sclerosis (ALS) (Miquel, et al, 2012; Palamiuc, et al, 2015; Valbuena, et al, 2016). Mouse models of ALS, due to mutations in Cu/Zn superoxide dismutase (SOD), have described the occurrence of a metabolic shift towards aerobic glycolysis, with upregulation of PDK and phosphorylation of PDC.…”
Section: Therapeutic Uses Of Dcamentioning
confidence: 99%
“…Recent studies have confirmed a direct role for leptin in Teff‐cell function and differentiation. T cell‐specific leptin receptor knockout mice have now been shown by two groups to be critical for T‐cell polarization into pro‐inflammatory Th1 and Th17 subsets which secrete inflammatory cytokines IFN‐γ and IL‐17, respectively . Indeed, Gerriets et al.…”
Section: T‐cell Dysfunction In Malnutritionmentioning
confidence: 99%
“…Indeed, Gerriets et al. demonstrated that both malnutrition‐associated hypoleptinemia and T cell‐specific leptin receptor knockout suppressed Th1 or Th17‐cell number and function . Moreover, both Reis et al.…”
Section: T‐cell Dysfunction In Malnutritionmentioning
confidence: 99%